A convenient method for the preparation of 20-[18O]-labeled ingenol. Issue 14 (5th April 2017) - Pospíšil, Jiří; Béres, Tibor; Strnad, Miroslav
Graphical abstract: Highlights: Short and efficient 2 step synthesis of labeled ingenol. Protecting group free introduction of the 18 O atom with excellent selectivity. Highly selective Mitsunobu reaction. 18 O2 -acetic acid as the 18 O atom source. Abstract: A short and efficient protecting group-free synthesis of isotopically labeled 20-[ 18 O]-ingenol has been developed. Based on a highly selective (only one out of four hydroxy groups) Mitsunobu reaction of ingenol with 18 O2 -acetic acid and subsequent methanolysis, this route yielded the desired 20-[ 18 O]-ingenol in high yield and chemical and isotopic purity.